2014
DOI: 10.5601/jelem.2013.18.4.552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sulfur fertilization on the concentrations of copper, zinc and manganese in the roots, straw and oil cake of rapeseed (Brassica napus L. ssp. oleifera Metzg)

Abstract: Sulfur application has a significant effect on the yield of oil bearing plants of the family Brassicaceae, especially when the sulfur content of soil is low. Sulfur fertilization also affects the value of plant raw materials, reflected by the concentrations of mineral and biologically active compounds in biomass. The aim of this study was to determine the effect of sulfur application to soil on the concentrations of copper, zinc and manganese in the root residues, straw and oil cake of winter and spring rapese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 6 publications
0
8
1
Order By: Relevance
“…Rape threshing residues demonstrated a higher Mn concentration after fertilisation with biogas production waste compost. During the experiment Mn concentration in spring oilseed rape seeds was marginally higher than that in threshing residues compared to the concentrations indicated by other researchers: 37.8-40.8 mg kg -1 in seeds and 10.2-20.9 mg kg -1 in threshing residues (Jankowski et al, 2014).…”
contrasting
confidence: 51%
See 2 more Smart Citations
“…Rape threshing residues demonstrated a higher Mn concentration after fertilisation with biogas production waste compost. During the experiment Mn concentration in spring oilseed rape seeds was marginally higher than that in threshing residues compared to the concentrations indicated by other researchers: 37.8-40.8 mg kg -1 in seeds and 10.2-20.9 mg kg -1 in threshing residues (Jankowski et al, 2014).…”
contrasting
confidence: 51%
“…Zinc concentrations determined in the primary and secondary plant produce during the experiment did not exceed the ones suggested by the majority of researchers, namely: in potato tubers -5.1-35.0 mg kg -1 , spring oilseed rape seeds -55.4 mg kg -1 and in threshing residues -11.5 mg kg -1 (Pollak, Favoino, 2004;Kabata-Pendias, 2011;Jankowski et al, 2014).…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…From the economic point of view, the production of winter oilseed rape generates direct profits from the sale of seeds and indirect profits by increasing the yield of successive crops, in particular, cereals [86]. Oilseed rape is an attractive preceding crop for cereals because field residues are rapidly decomposed (narrow C:N ratio), they are abundant in macronutrients and micronutrients, and act as biofumigation agents [87][88][89]. The seed yield of winter wheat increased by 0.8 to 1.5 Mg ha −1 when grown after winter oilseed rape than when cultivated in a continuous monoculture [90,91].…”
Section: Profitabilitymentioning
confidence: 99%
“…Another research (Kahraman et al, 2015) on nutritional quality of chickpea revealed that; in general, protein ratio and Mg content decreased under drought conditions while K and P had an increasing tendency. Furthermore, previous studies (Krzebietke and Sienkiewixz, 2010;Jankowski et al, 2014) reported that foliar application of chemicals on plants realized significant changes in the concentration of nutritional compounds Organic matter is quite important in nutrition of plants. It increases quality of soil, physical structure, aeration and supplementation of water, development of root.…”
Section: Resultsmentioning
confidence: 99%